2011
DOI: 10.1111/j.1540-8167.2010.01993.x
|View full text |Cite
|
Sign up to set email alerts
|

Total and Interatrial Epicardial Adipose Tissues Are Independently Associated With Left Atrial Remodeling in Patients With Atrial Fibrillation

Abstract: EAT(total) and thickness of periatrial EAT were significantly larger in AF subjects compared to those of the matched controls and were closely related to the chronicity of AF. Moreover, EAT(total) and IAS thickness were independently associated with LAV in subjects with AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 35 publications
6
80
0
2
Order By: Relevance
“…Thus, previous animal studies have shown that metabolic syndrome and obesity induce alterations of sinus node function due to fat accumulation around nodal cardiomyocytes and changes in sympathetic innervation [29,30]. Moreover, obesity associated increased leptin and reduced adiponectin levels might also contribute to increased atrial fibrosis [31]. Amongst the present study population 10 patients (9.4%) had PM implanted due to sinus arrest.…”
Section: Obesity and Metabolic Syndromementioning
confidence: 97%
“…Thus, previous animal studies have shown that metabolic syndrome and obesity induce alterations of sinus node function due to fat accumulation around nodal cardiomyocytes and changes in sympathetic innervation [29,30]. Moreover, obesity associated increased leptin and reduced adiponectin levels might also contribute to increased atrial fibrosis [31]. Amongst the present study population 10 patients (9.4%) had PM implanted due to sinus arrest.…”
Section: Obesity and Metabolic Syndromementioning
confidence: 97%
“…106 Furthermore, total epicardial adipose volume and thickness have both been associated with LA volume. 107 Although these associations do not necessarily prove a causal relationship between an inflammatory cascade driven by the epicardial tissue and the genesis of AF, extent of epicardial adipose tissue has also been related to AF recurrence after ablation 108 and may thus be a clinically useful marker in the evaluation of AF.…”
Section: Epicardial Adipose Tissuementioning
confidence: 99%
“…Recent studies clarified that EAT is a particular form of visceral adipose tissue that is in direct contact with the myocardium and acts as a biologically active endocrine organ, secreting several inflammatory cytokines, 7,8 which might promote atrial structural remodeling. 5 Generally, EAT volume has been shown to increase in patients with metabolic syndrome. 19 In fact, several recent large population-based cohort studies confirmed the association between metabolic syndrome and AF even after adjustment for possible confounding factors.…”
Section: Eat and Afmentioning
confidence: 99%